Coffee Table Inspired by Haidilao Hotpot - Lim, Keng Heng; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2023)
Heavy rainfall is common in Malaysia during the rainy season (October to March), resulting in flooding and, in some areas, flash flooding. Following the flood, various consequences occurred, including furniture destruction and the weight of maintaining or replacing new furniture. Therefore, the primary goal of this research is to determine the design criteria for a coffee table inspired by Haidilao hotpot, as well as to design and build a prototype of a coffee table inspired by Haidilao hotpot. The design criteria were derived from the questionnaire that disseminated online via Google form, with 50 people responding. The survey's primary subjects were Taman Angkasa Nuri residents. According to the findings, 100% of respondents favor water resilience coffee tables because their coffee table was destroyed during the flood incident. Furthermore, most respondents favor a contemporary coffee table with a light color, a square form with closed storage, and a mix of more than one material. Because of its water-resistance property, the prototype of coffee table in this study is made of stainless steel (frame) and tempered glass (top table). In conclusion, the suggested coffee table is critical for flood victims because it reduces the cost of purchasing or repairing the damage coffee table.